PENGARUH KESALAHAN WALI PADA KEABSAHAN PERNIKAHAN - Noor Efendy; Ainur Rahmah (Universitas Darunnajah Jakarta, Indonesia, 2024)
Marriage in Islam is an act of worship and is a sunnah recommended by the Prophet Saw. Marriage is a bridge for two families to stay in touch with each other, legalize the association between men and women, and as a place to continue offspring. As an act of worship, marriage has pillars and conditions that must be carried out so that the marriage is valid in the eyes of religion. One of the requirements in marriage is the guardian of the prospective woman. However, in reality in the community, there are still many cases of guardian error in a marriage. Some of the factors for guardian error are the lack of public knowledge about the pillars of marriage, the unknown whereabouts of the biological father, adopted children who never know about their status, and others. Guardian error affects the validity of the marriage and the marriage is considered defective. In Islamic law, KHI, and the Indonesian Marriage Law agree that the mistake of the guardian causes the marriage to be invalid and must be annulled and then remarry with the correct guardian in accordance with the predetermined order of guardians.